Pengaruh Dimensi Motivasi Belanja Hedonis terhadap Pembelian Impulsif pada Situs Marketplace Shopee - Misbah Arbaiah; Dorothy Rouly Pandjaitan; Dwi Asri Siti Ambarwati (Reviu Akuntansi, Manajemen, dan Bisnis, 2022)
Purpose: This research is based on the online shopping trend which has increased in Indonesia and the Shopee marketplace site which has experienced a very significant increase in sales from previous years. Research methodology: This study aims to analyze the effect of the Hedonic Shopping Motivation Dimension on impulse buying. The population in this study are consumers who have made impulse purchases on the Shopee marketplace site. The sample in this study was taken using a purposive sampling method and determined by the Bernoulli formula. Results: The results of this study indicate that Idea Shopping (X3), Social Shopping (X4), and Relaxation Shopping (X5) have a positive and significant effect on Impulsive Purchases on the Shopee marketplace site. The results of this study indicate that the variable that has the most dominant effect on impulse buying is relaxation shopping and the variable that has the least effect is social shopping. Limitations: This research focuses on experience, idea, value, social and relaxation as independent variables; and the competitive advantage as dependent variable. Contribution: This research explains the effect on Impulsive Purchases on the Shopee marketplace site and also the implications of marketing management theory.